Heterozygosity for TACI A144E causes haploinsufficiency and pneumococcal susceptibility in mice - Jabara, Haifa H. (J Allergy Clin Immunol, 2016)
BACKGROUND: The B cell receptor TACI is important for T-independent antibody responses. One in 200 blood donors are heterozygous for the TACI A181E mutation. OBJECTIVE: To investigate the impact on B cell function of TACI A181E heterozygosity in reportedly healthy subjects and of the corresponding TACI A144E mutation in mice. METHODS: Nuclear factor kappa B (NFκB) activation was measured by luciferase assay in 293T cells co-transfected with wild-type (WT) and mutant TACI. TACI driven proliferation, isotype switching and antibody responses were measured in B cells from heterozygous TACI A144E knock-in mice. Mouse mortality was monitored after intranasal pneumococcal challenge. RESULTS: The levels of natural antibodies to the pneumococcal polysaccharide component phosphocholine (PC) were significantly lower in A181E heterozygous than TACI sufficient Swedish blood donors never immunized with pneumococcal antigens. While overexpressed hTACI A181E and mTACI A144E acted as a dominant negative in transfectants, homozygosity for A144E in mice resulted in absent TACI expression in B cells, indicating that the mutant protein is unstable when naturally expressed. A144E heterozygous mice, like TACI(+/−) mice, expressed half the normal level of TACI on their B cells and exhibited similar defects in APRIL-driven B cell activation, antibody responses to TNP-Ficoll, production of natural antibodies to PC, and survival following intranasal pneumococcal challenge. CONCLUSION: These results suggest that TACI A181E heterozygosity results in TACI haploinsufficiency with increased susceptibility to pneumococcal infection. This has important implications for asymptomatic TACI A181E carriers.